Non-Litigation Resolution of Business Use Rights Disputes Between PT. Lebuni and Shareholders - Razak, Ferli; Dungga, Weny Almoravid; Mandjo, Julius T. (Universitas Negeri Gorontalo, 2022)
The purpose of this research is to find out the non-litigation settlement of the business use right dispute between PT Lebuni and the shareholders. The method used in this research is empris research method which is used as a method to examine a legal provision that applies, as well as how the realization and reality of these provisions in community life. The results of this research are The arable land dispute occurred between the Bukit Tinggi Village community and PT Lebuni Plantation. This dispute was triggered by an agreement between the directors of PT Lebuni and the community, in which of the 250 hectares of land registered in the Cultivation Rights Title, 150 hectares were given to farmers to work on, while 100 hectares were controlled directly by the company for industrialization purposes. The dispute arose when the Director of PT Lebuni decided to take control of the land cultivated by the farmers, which was their source of livelihood. This decision was taken to meet the needs of the company, but it has the potential to harm the farming community in Bukit Tinggi Village, because it ignores the distribution of land according to plantation use rights.